A Novel Potentially Pathogenic Rare Variant in the DNAJC7 Gene Identified in Amyotrophic Lateral Sclerosis Patients From Mainland China - Wang, Mengli; Liu, Zhen; Yuan, Yanchun; Ni, Jie; Li, Wanzhen; Hu, Yiting; Liu, Pan; Hou, Xiaorong; Huang, Ling; Jiao, Bin; Shen, Lu; Jiang, Hong; et al. (Frontiers in Genetics, 2020)
Variants in the DNAJC7 gene have been shown to be novel causes of amyotrophic lateral sclerosis (ALS). However, the contributions of DNAJC7 mutations in Asian ALS patients remain unclear. In this study, we screened rare pathogenic variants in the DNAJC7 gene in a cohort of 578 ALS patients from mainland China. A novel, rare, putative pathogenic variant c.712A>G (p.R238G) was identified in one sporadic ALS patient. The carrier with this variant exhibited symptom onset at a relatively younger age and experienced rapid disease progression. Our results expand the pathogenic variant spectrum of DNAJC7 and indicate that variants in the DNAJC7 gene may also contribute to ALS in the Chinese population.